Society Spotlight: China Bioanalysis Forum. (March 2013) - Tang, Daniel; Zhong, Dafang; Dong, Kelly; Hu, Pei; Liu, Huichen; Jiang, Hongliang; Du, Alicia
The China Bioanalysis Forum (CBF), a volunteer and science focused group, was recently formed. The formation of CBF is a response to the urgent needs of updating current Chinese bioanalytical guidelines, the harmonization of Chinese and international guidelines, and establishing a platform for scientific exchange within the Chinese bioanalytical community. The mission, organization and the future plan of CBF are discussed in this short communication.